THE USE OF GENE THERAPY THROUGH BEVACIZUMAB IN THE TREATMENT OF COLORECTAL CANCER AN INTEGRATIVE REVIEW - Lucas Santos de Oliveira, Tiago Silva Mendes, Anderson Bruno Souza dos Santos; Marisa Salvi; Marcus Vinícius Cardoso (Journal of Medical Care Research and Review, 2022)
Colorectal cancer is a pathology that affects the individual’s gastro-intestinal tract, affecting from the large intestine to the anus. The treatment of this cancer consists of surgical procedure, chemotherapy and radiotherapy. Currently, the combination of bevacizumab with traditional chemotherapy for CRC (colorectal cancer) has been used, since bevacizumab is a monoclonal antibody whose mechanism of action is to inhibit the growth of new blood vessels that would carry nutrients to the tumor. Treatment through gene therapy associated with bevacizumab has shown to be very promising in the treatment of colorectal cancer, seeking to reduce recurrences, mortality and toxicities caused by the treatment. The present study aimed to evaluate how the use of bevacizumab associated with gene therapy has shown promise in the treatment of colorectal cancer. For data collection, an integrative literature review was carried out, where through consultations in the databases, PubMed, SciELO (Scientific Electronic Library Online) and VHL(Virtual Health Libraries), articles published in the last 5 years were selected (period from 2016 to December of 2021). After selecting articles and data obtained, it is observed that gene therapy is able to make changes in specific genes, with the aim of decreasing the level of tumor growth, and can be used in conjunction with bevacizumab, thus increasing the percentage of survival of patients affected by this disease.